Capsaicin induces cytotoxicity in human osteosarcoma MG63 cells through TRPV1-dependent and -independent pathways. Issue 12 (18th June 2019) - Bao, Zhengqi; Dai, Xiusong; Wang, Peter; Tao, Yisheng; Chai, Damin
ABSTRACT: An accumulating body of evidence has shown that capsaicin induces apoptosis in various tumor cells as a mechanism of its anti-tumor activity. However, the effects of capsaicin on osteosarcoma have not been studied extensively. In the current study, we explore the molecular mechanism of capsaicin-mediated tumor suppressive function in osteosarcoma. We found that capsaicin-induced apoptosis and the activation of transient receptor potential receptor vanilloid 1 (TRPV1) in a dose- and time-dependent manner in human osteosarcoma MG63 cells in vitro . Blocking TRPV1 using capsazepine attenuated the capsaicin-induced cytotoxicity, mitochondrial dysfunction, overproduction of reactive oxygen species (ROS) and decrease in superoxide dismutase (SOD) activity. In addition, the results demonstrated that capsaicin induced the activation of adenosine 5ʹ-monophosphate-activated protein kinase (AMPK), p53 and C-jun N-terminal kinase (JNK). In addition, Compound C (antagonist of AMPK) attenuated the activation of p53, which appeared to be TRPV1 independent. Taken together, the present study suggests that capsaicin effectively causes cell death in human osteosarcoma MG63 cells via the activation of TRPV1-dependent (mitochondrial dysfunction, and overproduction of ROS and JNK) and TRPV1-independent (AMPK-p53) pathways. Thus, capsaicin may be a potential anti-osteosarcoma agent.